Decorating mesoporous silicon with amorphous metal–phosphorous-derived nanocatalysts towards enhanced photoelectrochemical water reduction. Issue 39 (22nd September 2016) - Zhang, Hefeng; Li, Ailong; Wang, Zhiliang; Ma, Weiguang; Li, Deng; Zong, Xu; Li, Can
Abstract : Herein, we presented a facile and universal synthetic route that can incorporate a series of amorphous metal–phosphorous-derived (denoted as M–P) HER catalysts with p-Si under ambient conditions. Abstract : Developing earth-abundant catalysts as alternatives to noble metals and facile approaches that can integrate catalysts to photoelectrodes for the hydrogen evolution reaction (HER) are critical for the successful application of solar-driven water splitting devices. Herein, we presented a facile and universal synthetic route that can incorporate a series of amorphous metal–phosphorous-derived (denoted as M–P) HER catalysts with p-Si under ambient conditions. An onset potential of +0.3 V vs. reversible hydrogen electrode (RHE) and a photocurrent density of ca. 20 mA cm −2 at 0 V vs. RHE were obtained under simulated AM 1.5G solar illumination (100 mW cm −2 ), and are among the best values ever reported for Si photocathodes decorated with noble-metal-free catalysts. This excellent performance is ascribed to the drastically reduced charge transfer resistance across the p-Si and electrolyte due to the combination of a high quality semiconductor/catalyst interface and highly active cocatalysts with an amorphous nature. Moreover, the M–Ps/p-Si photocathodes demonstrated excellent stability due to the protection afforded by the M–Ps catalysts that were intimately adhered to p-Si.